CLOT Analysis Based on SWOT and 4Ps - Pan, Zihang (Transactions on Social Science, Education and Humanities Research, 2024)
This paper aims to conduct an in-depth study of CLOT through SWOT analysis, and explore its internal strengths and weaknesses, external opportunities and threats. Through SWOT analysis, the internal advantages of CLOT are brand diversity and unique design, but there are also disadvantages in brand awareness and market competition. And use the 4P theory to analyze its strategic application in product, price, place and promotion. 4P theory is carried out to comprehensively understand the position and potential development direction of CLOT brand in the market competition. Through 4P theoretical analysis, CLOT has strong competitive advantages in product innovation, price positioning, place expansion and promotion strategy, but it needs to strengthen the international market layout and brand promotion. This study helps CLOT to deeply understand its position and potential development direction in the market and provides a reference for CLOT to formulate more effective marketing strategies and brand development plans in the future.